The Influence of Job Demand Altruism-oriented Culture Toward Job Performance with Burnout of Personnel at the Hospital in an Autonomous University - Viboonpin, Kuntika; Jadesadalug, Viroj (Dusit Thani College Journal, 2020)
The research was aimed 1) to study the influence of job demand toward job performance with burnout and altruism-oriented culture as a moderator variable 2) to study the influence of burnout toward job performance. This research was a quantitative research. The data is collected using questionnaires. The population group is 151 staff working in department of surgery, autonomous university. Hierarchical Multiple Regression Model were used to analyzed data. The result of first objective found that 1) work pressure has a positive influence with burnout (β=0.77) 2) work-family conflict has a negative influence with burnout (β=-0.49) 3) role overload has a negative influence with burnout (β=0.05) 4) altruism-oriented culture has a influence on the relationship between role overload and burnout and the result of the second objective found that burnout has a negative influence with performance (β=0.50).